2022
DOI: 10.1097/mpg.0000000000003670
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Diagnostic Delay for Children With Inflammatory Bowel Disease

Abstract: Objectives: Pediatric inflammatory bowel disease (IBD) is a complex inflammatory condition of the gut. Diagnosing IBD involves distinct longitudinal periods from first symptoms to primary care assessment, tertiary care referral, and then endoscopic confirmation. The term diagnostic delay (DD) is used if these periods are prolonged. The aim of this review was to amalgamate DD data for children with IBD, and identify factors associated with prolonged DD. Methods: Six health literature databases were searched (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
1
1
0
Order By: Relevance
“…The median diagnostic delay in our study was found to be 3 months for CD and 2 months for UC, consistent with findings from other studies that commonly report longer delays for CD compared to UC [17,18,[31][32][33][34][35][36][37]. Recent investigations from El Mouzan et al [31] and Sulkanen et al [17] found median delay for CD and UC at 8 and 5 months in Saudi Arabia, and 6.6 and 4.1 months in Finland, which is slightly longer compared to our study.…”
Section: Diagnostic Delays In Paediatric Ibdsupporting
confidence: 91%
“…The median diagnostic delay in our study was found to be 3 months for CD and 2 months for UC, consistent with findings from other studies that commonly report longer delays for CD compared to UC [17,18,[31][32][33][34][35][36][37]. Recent investigations from El Mouzan et al [31] and Sulkanen et al [17] found median delay for CD and UC at 8 and 5 months in Saudi Arabia, and 6.6 and 4.1 months in Finland, which is slightly longer compared to our study.…”
Section: Diagnostic Delays In Paediatric Ibdsupporting
confidence: 91%
“…One of the main findings was that PIBD children from the cohort were diagnosed earlier than children residing in Europe and Israel from the EUROKIDS registry (7.7 vs. 12.5 years in CD and 10.2 vs. 11.6 years in UC, respectively) [ 5 , 6 ]. Even with the increasing trend, time from the disease onset to the time of established IBD diagnosis in children and adults may take several months demonstrated in three recent systematic reviews [ 7 9 ]. Longer diagnostic delay has been associated with growth faltering, more extensive disease, and a worse response to treatment in children; [ 8 ] while a systematic review of 11 studies in 6,164 adults showed that delayed diagnosis was associated with higher chances of developing stricturing and penetrating disease, intestinal surgery in CD as well as colectomy in UC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%